Anxiety, depression and quality of life in family caregivers of palliative cancer patients during home care and after the patient's death - Götze, H.; Brähler, E.; Gansera, L.; Schnabel, A.; Gottschalk‐Fleischer, A.; Köhler, N. (European journal of cancer care, 2018)
We examined psychological parameters in family caregivers of palliative cancer patients before and after the death of the patients. Caregivers’ data about depression and anxiety (Hospital Anxiety and Depression Scale), quality‐of‐life (Short Form‐8 Health Survey), and social support (Oslo Social Support Scale) were collected at the beginning of home care (t1) and 2 months after the patient had died (t2). Regression models were employed to examine factors related to depression and anxiety in the bereaved caregivers. We interviewed 72 relatives, who were the primary caregiver of a patient. One‐third (31.9%) of caregivers had high anxiety levels and 29.2% had high depression levels (t1, cut‐off = 10). At t2, anxiety and depression had decreased significantly. There were no changes in quality‐of‐life over time. At both points of assessments, quality‐of‐life was lower than in the general population. Relevant factors for higher anxiety and depression in the bereaved caregivers were high levels of distress at t1, insufficient social support and low physical function. Bereaved caregivers were particularly depressed when they had been the spouse of the patient. Healthcare professionals should consider social isolation of caring relatives both during homecare and afterwards. Thus, it seems to be important to routinely offer support to spouses.